Ash-slag dumps with annual regulation differentiated flows of ash and slag coal power station - E. P. Khagleev (Известия высших учебных заведений: Проблемы энергетики, 2018)
Ash dumps of traditional types are permanent air and water environment pollution sources in which accumulated colossal amount of ash-slag waste by now. Stricter environmental requirements raise the question about existence of coal power stations in the future. A radical solution of the problem can be wide-scale ash-slag recycling. The ash-slag must supply to recycling plant in separate (in other words differential) form directly from coal power station boiler units and separate storing ash-slag dumps as well. The separate storing ash-slag dump would became a buffering hub adjusting differential ash and slag inflow during the year. In this case, an excessive amount of the ash and slag waste will be stored in winter season and unloading in summer by the separate storing ash-slag dump. The most complete recycling of ash-slag will give the possibility to unlimited prolong of dumps operation period, to reduce their maintenance cost and to improve the environmental situation in areas of the dumps location.